An unusual cause of gastrointestinal bleed in patients with liver cirrhosis. Issue 7 (10th July 2019) - Kulkarni, Anand V; Sharma, Manoj Kumar; Jamwal, Kapil Dev; Arora, Asit
Abstract : Acute upper gastrointestinal (UGI) bleeding in cirrhosis has been classically linked to variceal rupture, although peptic ulcer and portal hypertensive gastropathy-related bleed are not uncommon. Gastrointestinal stromal tumour (GIST) is the most common mesenchymal tumour and may also present as UGI bleed; however, there are no reports of GIST presenting as UGI bleed in patients with cirrhosis. Here, we report three cases of GIST who had presented with UGI bleed and were successfully managed with surgical excision and are tolerating imatinib without recurrence.